Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11743-015-1709-3
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Micellization and Interfacial Properties of Ionic Liquid‐Type Imidazolium Gemini Surfactant with Amphiphilic Drug Amitriptyline Hydrochloride and its Thermodynamics

Abstract: The thermodynamics of mixed micellization of amitriptyline hydrochloride (AMT) with ionic liquid-type imidazolium gemini surfactant ([C 10 -4-C 10 im] Br 2 ), was investigated at different mole fractions and temperatures by surface tension measurements. The deviation of the critical micelle concentration (CMC) from the ideal critical micelle concentration (CMC*), micellar mole fraction (X m 1 ) from ideal micellar mole fraction (X ideal 1 ), the values of interaction parameter (b) and activity coefficients (f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…The observed ΔGadsnormalo values are higher than normalΔGminnormalo values indicating the adsorption at the air–solution interface is more favourable than the formation of micelles in the bulk solution [52]. The ratio of normalΔGadsnormalo/normalΔGnormalmnormalo was found to be approximately 1.5 (table 3) for SDS-rich and DTAB-rich at different temperatures indicating less spontaneity in the transfer of the monomers to the interface [53].…”
Section: Resultsmentioning
confidence: 99%
“…The observed ΔGadsnormalo values are higher than normalΔGminnormalo values indicating the adsorption at the air–solution interface is more favourable than the formation of micelles in the bulk solution [52]. The ratio of normalΔGadsnormalo/normalΔGnormalmnormalo was found to be approximately 1.5 (table 3) for SDS-rich and DTAB-rich at different temperatures indicating less spontaneity in the transfer of the monomers to the interface [53].…”
Section: Resultsmentioning
confidence: 99%
“…The β m values of systems α 1 = 0.5 and α 1 = 0.7 are negative which means that the attractive interaction between the head groups of the two surfactants leads to stabilization due to electrostatic factor (10), but for system α 1 = 0.9 the β m value is positive which indicates a repulsive interaction, Maeda (14) suggested that the interaction between the chains of the two surfactants may play major role in addition to the interaction between the heads of surfactants in the formation of mixed micelles, especially for the dissimilar chain lengths. The values of activity coefficients, f 1 and f 2 obtained from equations 4 and 5 are less than 1 which meaning the non-ideal behavior of the studied binary systems except for α 1 system which shows a value greater than unity (15).…”
Section: = Exp[mentioning
confidence: 81%
“…ads /ΔG o m ) with Soaps. e observed ΔG o ads values are higher than ΔG o min values, indicating the adsorption at the air-solution interface is more favorable than the formation of micelles in the bulk solution [40]. e ratio of (ΔG o ads /ΔG o m ) is found in the range of 1.1 to 1.14 for LFBY, NM, OKT, LRL, and LX ( Figure 16).…”
Section: Correlation Of (δG Omentioning
confidence: 98%